The Analysis of Kurikulum Operasional Madrasah as the Implementation of Merdeka Curriculum - Lisan, Khusnul Harsul; Kholis, Adhan (JALL (Journal of Applied Linguistics and Literacy), 2024)
The Indonesian education landscape has experienced some significant changes in recent years to find out the best formula in its educational systems. The most recent is the implementation of Kurikulum Merdeka or Merdeka curriculum. This study aimed to analyze Kurikulum Operasional Madrasah (KOM) as the implementation of Merdeka curriculum in MAN 1 Bantul Yogyakarta. KOM is the school curriculum used by the school in applying the new curriculum during a year. The research used a qualitative method through a case study design. The research focused on the analysis of Kurikulum Operasional Madrasah and how was the format of the curriculum. In addition, it explored more about the teachers’ perception along with the challenges towards the implementation of Kurikulum Merdeka. The data collection involved interviews and document analysis providing valuable insights into the practical aspects of this curriculum reform. The data analysis consisted of data collection, data reduction, data display, and drawing conclusion. The findings highlighted the content of Kurikulum Operasional Madrasah focusing on giving the school more opportunities to adjust its characteristics, the students and its environment to achieve the goal of school vision and mission. Besides the teachers’ perception dealing with Merdeka Curriculum mostly said that although there were many challenges of the implementation, they agreed that this curriculum brought differences and many benefits in the teaching and learning process. This research hopefully contributes to the ongoing dialogues and cases related to the surrounding curriculum reforms in Indonesian Madrasah especially under the issues of Merdeka curriculum.